2018
DOI: 10.3389/fphar.2018.01019
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Danggui-Baizhu-Tang on High-Fat Diet-Induced Obesity in Mice by Activating Thermogenesis

Abstract: Danggui-Baizhu-Tang (DBT), a traditional Chinese medicine decoction, was used for decreasing serum TG and TC remarkably. However, effect of weight control and action mechanism remains confused. In this study, to evaluate the anti-obesity effects, different gradient concentration of DBT (0.59, 1.17 g/kg) or Orlistat (Orl, 15.6 mg/kg; positive control) were administrated by gavage for 8 weeks in C57BL/6J mice which were pretreated with chow or high fat diet (HFD) for 3 months. After administration, significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Moreover, orlistat and related drugs do not protect from the cardiovascular complications often associated with obesity and they ameliorate T2D only to a limited extent. Inhibition of PKDs in the intestine of mice or deletion and inactivation of PKD2 in animals led to similar protection from body weight gain as described previously for orlistat (Murtaza et al, 2017; Zhao et al, 2018), importantly, while we found that PKD2 inactivation or inhibition of PKDs increased stool lipid content, without any associated overt gastrointestinal disturbances or symptoms. A direct comparison of both drugs under standardized conditions would provide an overview of their relative efficiency and side effects.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, orlistat and related drugs do not protect from the cardiovascular complications often associated with obesity and they ameliorate T2D only to a limited extent. Inhibition of PKDs in the intestine of mice or deletion and inactivation of PKD2 in animals led to similar protection from body weight gain as described previously for orlistat (Murtaza et al, 2017; Zhao et al, 2018), importantly, while we found that PKD2 inactivation or inhibition of PKDs increased stool lipid content, without any associated overt gastrointestinal disturbances or symptoms. A direct comparison of both drugs under standardized conditions would provide an overview of their relative efficiency and side effects.…”
Section: Discussionsupporting
confidence: 90%
“…After Coicis Semen formula treating, rectal and BAT temperature were obviously elevated. Rectal temperature is corresponding to core body temperature (Meyer, Ootsuka, & Romanovsky, 2017), and based on our previous study (Zhao, Zhu, Cong, Yang, & Zhu, 2018), we speculated that energy expenditure was higher in Coicis semen formula-treated mice than that of the model mice.…”
Section: Discussionmentioning
confidence: 95%
“…Chinese medicines containing Atractylodes macrocephala Koidz. reduced the serum of total cholesterol (TC) and inflammatory cytokines and upgraded microbiota of the gut (Zhang et al, 2018;Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%